Integrating Indigenous Architectural Heritage into Mathematics Education: The Case of Baduy Leuit - Gida Kadarisma; Jagad Aditya Dewantara; Indah Puspita Sari; Anton Nasrullah; Soeharto Soeharto (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
This study aims to explore the potential of the Baduy leuit (traditional rice barns) as a cultural basis for designing mathematics tasks grounded in real-world contexts. Using an ethnographic approach, the research collected data through field observations, photographic and sketch documentation, direct measurements, and in-depth interviews with community elders. The findings reveal that the leuit embodies structural characteristics that correspond to fundamental geometric forms. Two principal types were identified: the Leuit Lenggang, resembling a truncated square pyramid, and the Leuit Gugudangan, resembling a rectangular prism. These structures offer authentic contexts for designing mathematics tasks related to volume, surface area, ratios, nets, and capacity estimation. Examples include calculating rice storage volume, determining bamboo requirements for construction, and analyzing roof coverage—all of which illustrate how traditional architecture can be transformed into meaningful mathematical problem situations. Beyond their mathematical relevance, the leuit reflects cultural values of food security, ecological stewardship, and collective responsibility, aligning with the Sustainable Development Goals (SDG 2: Zero Hunger; SDG 4: Quality Education; SDG 11: Sustainable Cities and Communities). The study concludes that integrating the Baduy leuit into mathematics task design offers a culturally responsive approach that enhances conceptual understanding while fostering appreciation of local wisdom.